An energyefficient virtual machine scheduler based on CPU sharereclaiming policy. (2015) - Xilong, Qu; Peng, Xiao
With the development of cloud computing, resource virtualisation technology has been widely applied for deploying largescale ITinfrastructures in many highperformance data centres. However, using virtualisation technology will also lead to some extra performance costs, especially when the cloud system is in the presence of mixedworkloads. In this paper, we present a novel virtual machine scheduling approach, namely sharereclaiming policy, in which the scheduler allows virtual machines to obtain extra CPU shares if they were frequently blocked by I/O interrupted recently. By this policy, shortterm I/Ointensive tasks will have more chances of being scheduled so as to compensate their performance losses caused by I/O operations. Extensive experiments are conducted by using various benchmarks; the results show that the proposed policy outperforms existing scheduling algorithm in the terms of energyefficiency, especially when the virtualised system is in the presence of intensive mixedworkloads.